PANGAN DI MALUKU UTARA, INDONESIA: KETERSEDIAAN, KETERKAITAN DAN DAMPAK EKONOMI - Samiun, Muhammad Zais M; Suparta, I Wayan; Hasnin, Muhammad (Universitas Pasundan, 2024)
The shift in economic structure has implications for food conditions and the food-producing sector, namely the agricultural sector. Therefore, this study aims to obtain a macro picture of food conditions, identify food availability and leading food commodities, and analyse the linkages and impacts of the food-producing sector in the economy. The analysis used descriptive approach, Location Quotient method and Input-Output model. The results of the analysis found that food conditions, especially food availability, experienced a drastic decline along with the decline in the role of the agricultural sector. However, it was identified that North Maluku has the potential for food availability and superior food commodities that can be developed in the form of superior food sweet potatoes, cassava, beans, vegetables and fruits. Furthermore, it is measured that food-producing sub-sectors have a much higher level of forward linkages and dispersion sensitivity, as well as the ability of the food-producing sector to create output multipliers, added value and income for the total economy. Both the food potential and input-output characteristics of the food sector are important measures in growing the food-producing agricultural sector. For this reason, policies that can be recommended through this research are balanced economic sector development models, especially ensuring their linkages with the agricultural sector, such as prioritising the development of the food processing industry sector. In addition, policy and financing support in the form of investment directives in the food sector are indispensable in the process.